THE IMPLEMENTATION OF CORPORATE GOVERNANCE IN ISLAMIC INSURANCE INSTITUTIONS IN INDONESIA BASED ON ISLAMIC FINANCIAL SERVICES BOARD STANDARD (IFSB) NO 8 - Siti Lisnawati; Ely Windarti Hastuti (Islamic Business and Management Journal, 2020)
This research presents the implementation of Good Corporate Governance (GCG) from international standards. The research discusses issues relating to financial disclosures carried out by Islamic insurance institutions in Indonesia. This research aims to analyze and understand the implementation of corporate governance in Islamic insurance institutions in Indonesia based on POJK Number 73/POJK.05/2016 and IFSB standards number 08. The research used secondary data obtained from the annual report for 2018. The research method used is qualitative by using a composite value calculation as a measure of GCG quality. The results of research indicate that the implementation of Corporate Governance in Islamic insurance in general have done good corporate governance which is marked with the result of self-assessment of every Islamic insurance which on average gets a good predicate. The results of research on the implementation of Corporate Governance based on IFSB standards, majority the standards have been implemented. These standards have been well implemented regarding the governance framework, the code of ethics and business conduct, the governance structure and the disclosure of relevant information. However, there are several points have not been applied or not yet disclosed in the annual report.